Crustal processes in volcanic systems : case studies from Northern Ireland, New Zealand, and Indonesia - Chadwick, Jane (Trinity College (Dublin, Ireland). Department of Geology, 2008)
It is evident that modification of primary melts from the mantle is significant in magma petrogenesis as primitive magmas are only rarely observed as erupted lavas at the Earth’s surface. Ascent and density filtering of primary arc magmas in the crust promotes modification of these melts by numerous processes, most importantly crystallisation and crustal contamination. However, modification can also be due to a combination of these processes, magma mixing and degassing. It is possible to identify the products of these processes in the resulting geochemistry of erupted magmas. However, these signals are often difficult to discern. Petrology and geochemistry provide a means of identifying and potentially quantifying igneous differentiation processes; whole rock major, trace element, and isotope data can be used to track changes and evolution of the magma systems. However, without careful ground-truthing using petrography and in-situ analytical techniques, whole-rock data may only represent a blurred average of a more complex record of processes. Utilising such petrological and geochemical techniques, this work evaluates variations in rock samples due to differentiation processes, specifically magma-crust interaction, operating beneath the three study areas; Slieve Gullion, Merapi Volcano, and the Taupo Volcanic Zone. These results are in the context of magmatic evolution in three different geo-tectonic settings; intra-plate (Ireland), continental (New Zealand) and oceanic arc volcanism (Java, Indonesia).
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin